Examining the Social Media Teacher-Student Interactions of Physical Education Teachers - Çağrı Hamdi Erdoğan; Ziya Bahadır; Ramazan Topuz (Türk Spor ve Egzersiz Dergisi)
The aim of this research is to examine the interactions between the physical education teachers and students in social media based on some variables. In the study, a descriptive survey method was used, which aimed at revealing the existing situation. The research group was comprised of 390 physical education teachers actively working at the state schools of Kayseri province in the 2018-2019 education year. Personal Information Form and Social Media Teacher – Student Interaction Scale were used in the study as the data collection tools. SPSS program was used in the analysis of the data. According to results of the research, it was determined that the social media teacher-student interaction levels of the physical education teachers were at the medium range. In addition, it was determined that virtual leader characteristics of physical education teachers were prominent. Also a significant difference was found concerning the social media teacher-student interaction levels of the physical education teachers for the variables school location, sport branch, physical education infrastructure in the school, the school team status, regular exercise, age, monthly income perception; however, statistically no significant difference was determined concerning the variables school type, marital status, and gender.